An empire of wealth : the epic history of american economic power - Gordon, John Steele ([S.l.] : HarperCollins, 2004)
Throughout time, from ancient Rome to modern Britain, the great empires built and maintained their domination through force of arms and political power. But not the United States. America has dominated the world in a new, peaceful, and pervasive way -- through the continued creation of staggering wealth. In this authoritative, engrossing history, John Steele Gordon captures as never before the true source of our nation's global influence: wealth and the capacity to create more of it. This P.S. edition features an extra 16 pages of insights into the book, including author interviews, recommended reading, and more.